2022
DOI: 10.1101/2022.05.11.491453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translocator protein is a marker of activated microglia in rodent models but not human neurodegenerative diseases

Abstract: Microglial activation plays central roles in neuro-inflammatory and neurodegenerative diseases. Positron emission tomography (PET) targeting 18kDa Translocator Protein (TSPO) is widely used for localising inflammation in vivo, but its quantitative interpretation remains uncertain. We show that TSPO expression increases in activated microglia in mouse brain disease models but does not change in a non-human primate disease model or in common neurodegenerative and neuroinflammatory human diseases. We describe gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 89 publications
0
5
1
1
Order By: Relevance
“…[79][80][81][82] Recent studies in rodent models suggest that TSPO signal may be related more to microglial number than microglial activation. 83 Although our observations suggest that increased TSPO signal reflects central inflammation and correlates with cognitive measures, the TSPO signal we observed does not reveal which cell types are responsible. Additionally, second generation TSPO ligands, including 18 F-DPA-714, are affected by the SNP rs6971 genotype.…”
Section: Discussioncontrasting
confidence: 70%
“…[79][80][81][82] Recent studies in rodent models suggest that TSPO signal may be related more to microglial number than microglial activation. 83 Although our observations suggest that increased TSPO signal reflects central inflammation and correlates with cognitive measures, the TSPO signal we observed does not reveal which cell types are responsible. Additionally, second generation TSPO ligands, including 18 F-DPA-714, are affected by the SNP rs6971 genotype.…”
Section: Discussioncontrasting
confidence: 70%
“…Beyond AD-related protein deposition, our method can also investigate the influence of other critical factors. It has been hypothesized, and to some extent observed 6, 7, 15 , that microglial activation (a probable marker for neuroinflammation 35, 50 ) affects excitability and neuronal activity in AD. Consequently, we performed a set of complimentary experiments where we recreated the obtained results in a model that also considers deviations to neuronal excitability due to microglial activation –measured with 18kDa Translocator Protein PET.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent preprint suggested that -in humans -TSPO-targeted radiotracers reflect microglial density rather than activated microglia. 54 Also, it is well-acknowledged that TSPO is expressed in other cell types than microglia. 23 These methodological issues may limit the conclusions that can be drawn from our results.…”
Section: Discussionmentioning
confidence: 99%